Evolutionary debunking arguments in ethics - Mogensen, A (2014)
I consider whether evolutionary explanations can debunk our moral beliefs. Most contemporary discussion in this area is centred on the question of whether debunking implications follow from our ability to explain elements of human morality in terms of natural selection, given that there has been no selection for true moral beliefs. By considering the most prominent arguments in the literature today, I offer reasons to think that debunking arguments of this kind fail. However, I argue that a successful evolutionary debunking argument can be constructed by appeal to the suggestion that our moral outlook reflects arbitrary contingencies of our phylogeny, much as the horizontal orientation of the whale’s tail reflects its descent from terrestrial quadrupeds. An introductory chapter unpacks the question of whether evolutionary explanations can debunk our moral beliefs, offers a brief historical guide to the philosophical discussion surrounding it, and explains what I mean to contribute to this discussion. Thereafter follow six chapters and a conclusion. The six chapters are divided into three pairs. The first two chapters consider what contemporary scientific evidence can tell us about the evolutionary origins of morality and, in particular, to what extent the evidence speaks in favour of the claims on which debunking arguments rely. The next two chapters offer a critique of popular debunking arguments that are centred on the irrelevance of moral facts in natural selection explanations. The final chapters develop a novel argument for the claim that evolutionary explanations can undermine our moral beliefs insofar as they show that our moral outlook reflects arbitrary contingencies of our phylogeny. A conclusion summarizes my argument and sets out the key questions that arise in its wake.